Quantitative phosphoproteomic analysis of RIP3‐dependent protein phosphorylation in the course of TNF‐induced necroptosis. Issue 6 (20th February 2014) - Zhong, Chuan‐Qi; Li, Yuanyue; Yang, Daowei; Zhang, Na; Xu, Xiaozheng; Wu, Yaying; Chen, Jinan; Han, Jiahuai
Abstract : Tumor necrosis factor (TNF) induced cell death in murine fibrosarcoma L929 cells is a model system in studying programed necrosis (also known as necroptosis). Receptor interacting protein 3 (RIP3), a serine–threonine kinase, is known to play an essential role in TNF‐induced necroptosis; however, the phosphorylation events initiated by RIP3 activation in necroptotic process is still largely unknown. Here, we performed a quantitative MS based analysis to compare TNF‐induced changes in the global phosphoproteome of wild‐type ( RIP3 +/+ ) and RIP3‐knockdown L929 cells at different time points after TNF treatment. A total of 8058 phosphopeptides spanning 6892 phosphorylation sites in 2762 proteins were identified in the three experiments, in which cells were treated with TNF for 0.5, 2, and 4 h. By comparing the phosphorylation sites in wild‐type and RIP3‐knockdown L929 cells, 174, 167, and 177 distinct phosphorylation sites were revealed to be dependent on RIP3 at the 0.5, 2, and 4 h time points after TNF treatment, respectively. Notably, most of them were not detected in a previous phosphoproteomic analysis of RIP3‐dependent phosphorylation in lipopolysaccharide‐stimulated peritoneal macrophages and TNF‐treated murine embryonic fibroblasts (MEFs), suggesting that the data presented in this report are highly relevant to the study of TNF‐induced necroptosis of L929 cells.